Shale Brazilian split test and numerical simulation of the discrete element method. Issue 2 (October 2020) - Wang, Jiong; Wang, Yang; Gong, Weili; Wang, Zhaoxuan
Abstract: This study performs a shale Brazilian split test by setting the loading and bedding directions at different angles to study the effect of anisotropy caused by the bedding structure and heterogeneity caused by different particles on the mechanical properties of shale. The results indicate that the cracks of the specimens splitting and breaking at 0° and 90° all extend vertically through the disk. A combination of Neper and 3DEC software is applied to the numerical simulation study of the shale splitting process through the discrete element method. The shale splitting failure modes are divided into three categories. At 0° and 90°, the cracks extend linearly through the loading ends, and the models show bedding and particle tensile failures, respectively. At 15°, the cracks run diagonally through the rock sample from the end of the upper loading section, parallel to the bedding direction. At 30° to 75°, the cracks propagate from the loading end along the parallel bedding direction. The experiments and numerical simulations verify that bedding influences the shale splitting failure mode and the mechanical behavior. Therefore, the investigation of the mechanical problems caused by the destruction of shale gas mining has a far-reaching significance.